More corporate action based on CEO narcissism character - Edi, Edi; Meiliana, Meiliana; Tanza, Evelyn (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Purpose – This research finds out the effect of a firm reputation on international acquisition with international acquisition experiences and CEO narcissism as moderating variables.Design/methodology/approach – Research data samples are companies on the Indonesia stock exchange between 2018 till 2021. To select the research sample, this research conducted purposive sampling.Findings – The results of this study show that Experience of International Acquisition and CEO Narcissism can moderate the effect of a firm reputation on international acquisitions. This research also found that CEO Narcissism can be the moderating variable for firm reputation and international acquisitions.Research limitations/implications – The limitation of this research is the object of this research are focusing on cross-border acquisitions. While still there are companies making domestic acquisitions and rarely do cross-border acquisitions, so the data sought is limited and it takes time to find the data. The data can only be accessed via Google and a lot of data is blocked, so it makes it less effective in finding the data needed for research. And some data needed is paid data so it is difficult to access.Practical implications – The practical implications of this study contributes to helping management when conducting mergers and acquisitions. Management shall be adding CEO narcissism as a new requirement for new recruitment standards. If a CEO has a highly narcissistic character, it will bring more acquisition and merger chances to the company. Adding the prospective CEO’s narcissism will simplify the company for deciding to recruit prospective CEO.Originality/value – The value of this research are using CEO narcissism and LQ45 which is still a new research topic in acquisition research.